A fluorogenic H2S-triggered prodrug based on thiolysis of the NBD amine. Issue 19 (1st October 2019) - Xie, Yonghui; Huang, Haojie; Ismail, Ismail; Sun, Hongyan; Yi, Long; Xi, Zhen
Graphical abstract: Abstract: Based on thiolysis of the NBD amine, a H2 S-triggered prodrug has been designed and synthesized for localized production of ciprofloxacin under micromolar H2 S. Activation of the prodrug can be monitored through fluorescence in real-time. We envision that thiolysis of the NBD amine could be readily used for development of other H2 S-triggered prodrugs in the future.